PID controller tuning via multi-scale control scheme for parallel cascade processes - Nandong, Jobrun; Zang, Zhuquan (2014)
This paper presents a new PID controller tuning formula constructed based on the Multi-Scale Control (MSC) Scheme. The proposed PID tuning formula is applicable to a process which can be approximated by a first-order plus deadtime (FOPDT) or second-order plus zero (SOPZ) model. A simple algorithm is proposed for applying the PID tuning formula to parallel cascade processes. The parallel cascade control structure is often used in process industry to overcome the limitation imposed by long time delay. Numerical study shows that the proposed scheme gives improved performance robustness over an IMC-based scheme for parallel cascade processes. © 2014 IEEE.